2022
DOI: 10.1186/s12903-022-02055-y
|View full text |Cite
|
Sign up to set email alerts
|

A survey on knowledge and attitudes towards molar-incisor hypomineralization among undergraduate and postgraduate students at the School of Stomatology, Wuhan University

Abstract: Background Molar incisor hypomineralization (MIH) is a developmental dental disease, and its clinical management challenges dentists. This study aimed to investigate the knowledge about MIH and the attitudes towards learning more about MIH among undergraduate and postgraduate students attending the School of Stomatology, Wuhan University. Methods This survey was based on a questionnaire modified based on previous studies. The questionnaire was sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Residents are required to attend theoretical training lectures related to clinical practice on a regular basis at the School of Stomatology, Wuhan University. Previous surveys also found such a lack of knowledge mastery in dental education [ 16 , 17 ]. Our findings indicated that the activity and problem-based learning of undergraduates and residents should be encouraged and enhanced during clinical practice education.…”
Section: Discussionmentioning
confidence: 94%
“…Residents are required to attend theoretical training lectures related to clinical practice on a regular basis at the School of Stomatology, Wuhan University. Previous surveys also found such a lack of knowledge mastery in dental education [ 16 , 17 ]. Our findings indicated that the activity and problem-based learning of undergraduates and residents should be encouraged and enhanced during clinical practice education.…”
Section: Discussionmentioning
confidence: 94%
“…Through studies that assess knowledge, practices, and attitudes, undergraduate dental students have expressed that one of the greatest difficulties with respect to MIH is its diagnosis and classification 6 . In a sample of 368 students, Liu and He found that only 20% feel that they have the ability to properly classify MIH 21 . Additionally, 90% of students expressed that there is a need to incorporate MIH into the course curriculum, emphasizing clinical features, differential diagnosis, and treatment options 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of 368 students, Liu and He found that only 20% feel that they have the ability to properly classify MIH 21 . Additionally, 90% of students expressed that there is a need to incorporate MIH into the course curriculum, emphasizing clinical features, differential diagnosis, and treatment options 21 . Based on their results and analysis, the authors signal the importance of conducting comprehensive and systematic training in the undergraduate course 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations